Polystichum hainanicola (Dryopteridaceae), a new fern species from Hainan Island, China - Zhang, Liang; Gao, Xin-Fen; Zhang, Li-Bing (Phytotaxa, 2013)
A new fern species, Polystichum hainanicola belonging to section Haplopolystichum (Dryopteridaceae), is described and illustrated from Hainan, the southernmost province of China. Polystichum hainanicola is most similar to P. guangxiense, but the former has pinnae with a length to width ratio of 2.5–2.7, lamina completely fertile and sori fewer than four above midrib of middle pinnae. In contrast, the latter has pinnae with a length to width ratio of ca. 3:1, lamina sterile in its lower portion and sori 6–11 above midrib of middle pinnae.